Variability in Colletotrichum curcumae, the incitant of leaf spot of turmeric (Curcuma longa L.) in Vidarbha, Maharashtra, India - GHURDE, M Y PALARPAWAR, V R (Journal of Spices and Aromatic Crops, 1995)
Colletotrichum curcumae, the incitant of leaf spot of turmeric (Curcuma longa L.) was found to exist in the form of three different strains in Vidarbha region of Maharashtra, India which could be distinguished by their symptom expression on Waigaon variety of turmeric. These strains differ in their cultural, morphological and physiological characters. Strains 1 and 3 were more virulent than Strain 2. Strain 1 produced symptoms on turmeric flowers also.